MODEL OCEAN DAN KINERJA KARYAWAN : PERAN MEDIATOR KETERLIBATAN KERJA - Ida Bagus Arindra Dirasthya; Meiliani Meiliani; Jahja Hamdani Widjaja (JWM (JURNAL WAWASAN MANAJEMEN), 2021)
The study aimed to investigate the mediation role of the work engagement in the relationship between the big five personality traits model (called OCEAN Model) and the employees’ performances. The study surveyed 70 employees using an online questionnaire. The results showed that each of the dimensions of the big five personality had no effect on the performance significantly. Individualy, the openness, the conscientiousness, the extraversion, however, statistically had a positive direction on the work performances. Conversely, the agreeableness and the neuroticism had a negative direction on the performances. The conscientiousness and the agreeableness influenced positively and significantly the work engagement. The extraversion showed the negative direction and insignificant. The other three components did not have a significant impact and has a positive direction. The work engagement was positively and significantly impact on the performances. The work engagement did not mediate the relationship between the personality dimensions of the openness, the conscientiousness, the extraversion, and the neuroticism and the employees’ performances. On the contrary, the work engagement mediated the influence of the the agreeableness on the work performances. The agreeableness component had a full mediation by the work engagement. It showed that the dimension of the agreeableness had the greatest influence on the employees’ performances. It seems that the employees work as their routines without motivation to do more. They should be strengthened their personality and more engaged in in their work to show their work performances